Rendez-Vous laparoendoscopic after ERCP failure in patient with Billroth II gastrectomy - Kreve, Fernanda (2019)
Endoscopic retrograde cholangiopancreatography (ERCP) is the treatment of choice in patients with choledocholithiasis. However, despite its high success rate, in some cases it is not successful, requiring alternative therapy. Billroth II partial gastrectomy is a condition associated with an important failure rate of ERCP. When endoscopic treatment fails, surgical exploration of the bile duct is the most common approach. However, the surgery is related to a greater complexity of execution and morbimortality. We describe the case of a patient with choledocholithiasis and Billroth II partial gastrectomy, submitted to the combined treatment called rendez-vous laparoendoscopic, after failure of ERCP, which unites in a single stage the endoscopic treatment of choledocholithiasis and laparoscopic removal of the gallbladder. We conclude that this therapeutic approach was effective, safe, with low cost and without complications.